Anaesthetic Effects of Ropivacaine and Bupivacaine on Onset, Duration of Block and Changes in Hemodynamic Parameters in Patients Undergoing Below Elbow Surgeries Under Ultrasound Guided Supraclavicular Brachial Plexus Block - Amatya, Bishwo Ram; Rayamajhi, Mallika; Thapa, Puja; Shah, Aashish; Rijal, Thaneshwar; Khadka, Anjan; Shrestha, Shova (Journal of Nepal Health Research Council, 2023)
Background: Supraclavicular brachial plexus block is commonly used regional anesthetic technique for below elbow upper limb surgeries. Ultrasound and nerve stimulator are used for higher success rates and fewer complications. Ropivacaine has been used as an alternative to Bupivacaine for rapid onset and longer duration along with lesser or no cardiac and neurotoxicity.The study was conducted with objective of assessing sensory and motor block characteristics of Bupivacaine and Ropivacaine in terms of onset, duration and adverse effects. Methods: A prospective observational study lasting three month duration from 15th February, 2022 to 14th May, 2022 was conducted among 60 patients divided by convenient sampling method into 30 in Group R (0.2% Ropivacaine 30 ml) and 30 in Group B (0.2% Bupivacaine 30 ml) undergoing below elbow orthopedic surgery under ultrasound and peripheral nerve stimulator guided supraclavicular brachial plexus block. Results: Block using Ropivacaine as compared to Bupivacaine had faster sensory onset in minutes (7±3.37 vs. 10.17±3.34; P value 0.0005), faster motor onset in minutes (10.17±5 vs. 22.33±5.04), shorter duration of sensory block in minutes (437.16±55.54 vs. 633.38±58.33), shorter duration of motor block in minutes (411±57.15 vs. 698.16±47.89), shorter time required for rescue analgesia in minutes (78.66±25.56 vs. 73.83±21.11) and no complications. Conclusions: 0.2% Ropivacaine can be used as an alternative to 0.2% Bupivacaine in below elbow upper limb orthopaedic surgeries under ultrasound and nerve stimulator guided supraclavicular brachial plexus block for rapid onset of sensory block and early regression of motor block. Keywords: Brachial plexus block; nerve stimulator; supraclavicular; ultrasound